Attachment Dimensions and Spatial Navigation in Female College Students: The Role of Comfort With Closeness and Confidence in Others - Rocha, Nuno Barbosa; Lemos, Andreia; Campos, Carlos; Rocha, Susana; Yamamoto, Tetsuya; Machado, Sérgio; Murillo-Rodriguez, Eric (Frontiers in Psychology, 2019)
Altered attachment characteristics may disturb the HPA and can even cause changes in the hippocampus. However, it is unknown if that will influence spatial navigation performance, learning and recalling. In this study we pretend to verify if there are differences in spatial navigation learning and was associated with attachment style dimensions of anxiety and close-depend. Sixty-five female participants were recruited and were evaluated using the Adult Attachment Scale-R and tested on a virtual maze navigation task (VMT) at one moment (exploratory trial + 3 trials) and 24h later (3 trials). There was a significant Moment x Trial x Close-Depend interaction for the outcome time, F (2, 126) = 3.807, p = 0.025, with post-hoc analysis indicating that the High Close-Depend group displayed significant improvements between Trial 1 and Trial 3 in the post-test assessment. Conversely, the Low Close-Depend group displayed significant improvements between Trial 1and Trial 3 but on the pre-test assessment. Furthermore, the Low Close-Depend group presented significant better performance in pre-test Trial 3 in comparison to the High Close-Depend group. Thereby, it seems that low comfort with proximity and trust in others is associated with reduced spatial navigation recall, although spatial learning performance was actually superior in these participants. It is possible that reduced exposure to social interaction and meaning relationship may be reduced in the Low Close-Depend group, leading to modifications in hippocampal function and, ultimately, reduced spatial recall. Conversely, participants with high comfort with proximity and trust in others may not display typical spatial learning in the proposed task as they are more willing to freely explore the presented environment.